The interpretability of doctor identification badges in UK hospitals: a survey of nurses and patients. Issue 7 (5th March 2014) - Hickerton, Bethan C; Fitzgerald, Daniel John; Perry, Elizabeth; De Bolla, Alan R
Abstract : Introduction: Hospital badges have multiple important purposes, but their essential role remains the clear identification of the bearer, including their professional status. The modernisation of medical careers in the National Health Service has changed terminology dramatically, resulting in a plethora of new job titles emerging among both doctors and nurses. Objective: To determine whether the new or old terminology allowed clearer identification of medical doctors by patients and nurses. Method: We replicated 11 identification badges used in the Royal Cornwall Hospital and Wrexham Maelor Hospital, both current and before the introduction of new medical training terminology. Data were collected from 114 patients and 67 nurses, by asking them to (1) identify which name badges represented doctors and (2) rank them in order of seniority. Results: Only 11% of patients and 60% of nurses identified a 'Foundation Year 1 Trainee' as a qualified medical doctor. Indeed, only 'General Practice Vocational Trainee' and 'Consultant' were both readily identifiable as qualified doctors to both patients and nurses. Ranking was also a problem, with only 19% of patients and 45% of nurses able to correctly grade medical doctors using the current terminology. The old terminology allowed more accurate identification by nurses, with over 80% successfully ranking and marking the title appropriately. Conclusions: Current terminology is a source of confusion to both patients and members of the immediate medical care team, with nurses unable to correctly identify medical doctors. Our study indicates that a review of terminology is necessary to ensure patients, and staff, are able to communicate effectively.